2019
DOI: 10.1098/rspb.2019.0353
|View full text |Cite
|
Sign up to set email alerts
|

Swimbladder morphology masks Southern Ocean mesopelagic fish biomass

Abstract: Within the twilight of the oceanic mesopelagic realm, 200–1000 m below sea level, are potentially vast resources of fish. Collectively, these mesopelagic fishes are the most abundant vertebrates on Earth, and this global fish community plays a vital role in the function of oceanic ecosystems. The biomass of these fishes has recently been estimated using acoustic survey methods, which rely on echosounder-generated signals being reflected from gas-filled swimbladders and detected by transducers on vessels. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…It has been observed that these factors present a strong variability across species and life stages (Davison et al, 2015). In particular, a recent study conducted in the Southern Ocean highlighted how, going from sub-Antarctic to Antarctic waters, the proportion of mesopelagic fish with a gas-filled swim bladder -and therefore the biomass estimated from acoustics-decreased while the biomass measured by midwater trawling remained approximately constant (Dornan et al, 2019). It is therefore important to emphasize that the patterns in acoustic backscattering we identify in this study may result from differences in micronekton biomass, community composition, or fish physiology.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that these factors present a strong variability across species and life stages (Davison et al, 2015). In particular, a recent study conducted in the Southern Ocean highlighted how, going from sub-Antarctic to Antarctic waters, the proportion of mesopelagic fish with a gas-filled swim bladder -and therefore the biomass estimated from acoustics-decreased while the biomass measured by midwater trawling remained approximately constant (Dornan et al, 2019). It is therefore important to emphasize that the patterns in acoustic backscattering we identify in this study may result from differences in micronekton biomass, community composition, or fish physiology.…”
Section: Discussionmentioning
confidence: 99%
“…Some species, in fact, do not have one or some lose the gas component in the adulthood. In addition, other organisms at midwater depths, e.g., siphonophores, possess gas-filled organ, which might be subsumed to the biomass from fish, leading to an overall overestimation of the midwater fish biomass (Kaartvedt et al, 2012;Davison et al, 2015;Dornan et al, 2019). Last, the relationship between targetstrength (an acoustic parameter) and biomass can introduce a potential bias in the estimate of the biomass (Saunders et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The Northern Central Pacific ecoregion appears to hold high mesopelagic fish diversity and a dominant abundance of fish in the genus Cyclothone (Clarke, 1973(Clarke, , 1974(Clarke, , 1976Maynard et al, 1975;Barnett, 1983). Despite high abundances of Cyclothone collected in trawls, several species within this genus have regressed or fat-invested swim bladders (Phleger, 1998;Davison, 2011;Dornan et al, 2019), rendering them weak acoustic scatterers. Thus, Cyclothone may not contribute significantly to the acoustic backscatter we observed and could be considered "acoustically cryptic" (Dornan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%